1992
DOI: 10.1111/j.1443-1661.1992.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Ulceration in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is frequently accompanied by peptic ulceration. Recent studies strongly suggest that the major cause is hypersecretion of gastric juice induced by hypoxemia or hypercapnia. To determine the incidence of peptic ulcers in COPD, we surveyed 267 patients with COPD seen at our hospital as inpatients or outpatients between 1984 and 1988. There were 90 patients with pulmonary emphysema, 93 with chronic bronchitis, and 84 with bronchiectasis. The prevalence of gastric ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that COPD is associated with an increased risk of rebleeding in patients with PUB [2931]. Some reasons that may explain why COPD increases the risk of PUB are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that COPD is associated with an increased risk of rebleeding in patients with PUB [2931]. Some reasons that may explain why COPD increases the risk of PUB are as follows.…”
Section: Discussionmentioning
confidence: 99%